Clinical Metagenomics: a New Approach to Diagnostics of Infectious Diseases - V. V. Gostev; L. I. Gelezova; P. S. Chulkova; A. A. Avdeeva; O. S. Kalinogorskaya; V. A. Ageevets; I. A. Tsvetkova; A. V. Zhuravlev; S. V. Sidorenko (Антибиотики и Химиотерапия, 2025)
Globally, infectious diseases continue to be one of the leading causes of death, even in the face of substantial advancements in basic biological and medical sciences. Diagnostics of life-threatening conditions, including bacteremia, sepsis, meningitis, and encephalitis, is frequently constrained by the low sensitivity associated with culture methods. The application of PCR and various serological methods is constrained by a defined set of specific primers, DNA probes, antibodies, and antigens that are restricted to a limited range of potential pathogens. The accuracy and timeliness of laboratory diagnostics for infectious diseases are critical. In the past decade, a new discipline has emerged — clinical metagenomics, representing a novel approach in medical microbiology. Because clinical metagenomics can identify potentially any pathogen, regardless of its biological nature, it is a hypothesis-free diagnostic approach. The benefits and efficiency of using metagenomic methods of sequencing to identify bacterial, viral, fungal, and parasitic pathogens of infectious diseases in humans are discussed in this review.